The Effect of Probiotics on Radiation Enteritis in Endometrial Cancer Patients Undergoing Radiotherapy - Godong, Bernardine; Ratna Mutumanikam, Nurul; Sunardi, Diana (HM Publisher, 2024)
Introduction: Radiation enteritis is damage to the small and large intestines caused by radiation therapy for regional cancer treatment. The incidence is around 90% in patients undergoing radiation in the pelvic and abdominal regions. This study aimed to report the effect of probiotics on radiation enteritis in endometrial cancer patients. Case presentation: A 57-year-old morbidly obese woman diagnosed with endometrial cancer underwent chemoradiation therapy. On the 21st out of 25 radiation sessions and the 2nd chemotherapy session, the patient visited the nutrition clinic at the Radiation Oncology Therapy Center with a complaint of diarrhea for the past 5 days. The diarrhea occurred approximately 10 times a day, with each bowel movement being approximately 50 ml and yellow in color. The patient was then treated with anti-diarrheal therapy, probiotics (Lactobacillus acidophilus, Bifidobacterium longum, and Streptococcus thermophilus) 2 times a day, zinc 20 mg once a day, and prescribed a low-fat and lactose-free diet. After monitoring on the 21st day, the frequency of liquid bowel movements decreased to 2 times a day, and the appetite improved. Conclusion: Patients with radiation enteritis who are given probiotics may experience a reduction in symptoms of acute diarrhea. Direct administration of probiotics increases beneficial bacteria in the digestive tract.